Strain-Dependent Effect of Macroautophagy on Abnormally Folded Prion Protein Degradation in Infected Neuronal Cells - Ishibashi, Daisuke (PLoS One, 2015)
Prion diseases are neurodegenerative disorders caused by the accumulation of abnormal prion protein (PrP(Sc)) in the central nervous system. With the aim of elucidating the mechanism underlying the accumulation and degradation of PrP(Sc), we investigated the role of autophagy in its degradation, using cultured cells stably infected with distinct prion strains. The effects of pharmacological compounds that inhibit or stimulate the cellular signal transduction pathways that mediate autophagy during PrP(Sc) degradation were evaluated. The accumulation of PrP(Sc) in cells persistently infected with the prion strain Fukuoka-1 (FK), derived from a patient with Gerstmann–Sträussler–Scheinker syndrome, was significantly increased in cultures treated with the macroautophagy inhibitor 3-methyladenine (3MA) but substantially reduced in those treated with the macroautophagy inducer rapamycin. The decrease in FK-derived PrP(Sc) levels was mediated, at least in part, by the phosphatidylinositol 3-kinase/MEK signalling pathway. By contrast, neither rapamycin nor 3MA had any apparently effect on PrP(Sc) from either the 22L or the Chandler strain, indicating that the degradation of PrP(Sc) in host cells might be strain-dependent.